Using Morphological Binary Images Operations for Automate Rotation Fill-In Estimation in Ultrasound Elastography Medical Imaging - Galaz-Donoso, B (Optica Publishing Group (formerly OSA), 2018)
We present an automate estimation method of rotation fill-in signature based on morphological binary image operations of elastographic images. The method is tested by Finite-Element simulations and then validated by in-vitro experiments. © 2018 The Author(s).